2018
DOI: 10.1111/1754-9485.12828
|View full text |Cite
|
Sign up to set email alerts
|

Computer vs human: Deep learning versus perceptual training for the detection of neck of femur fractures

Abstract: Introduction: To evaluate the accuracy of deep convolutional neural networks (DCNNs) for detecting neck of femur (NoF) fractures on radiographs, in comparison with perceptual training in medically-na€ ıve individuals. Methods: This study extends a previous study that conducted perceptual training in medically-na€ ıve individuals for the detection of NoF fractures on a variety of dataset sizes. The same anteroposterior hip radiograph dataset was used to train two DCNNs (AlexNet and GoogLeNet) to detect NoF frac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
76
0
4

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 120 publications
(84 citation statements)
references
References 20 publications
4
76
0
4
Order By: Relevance
“…However, studies using CNNs in the field of orthopedic surgery and traumatology are limited and the field is immature. So far, there are radiographic studies using CNNs for hip fractures (Adams et al 2019, Badgeley et al 2019, Cheng et al 2019, Urakawa et al 2019, distal radius fractures (Kim and MacKinnon 2018, Gan et al 2019, Yahalomi et al 2019, Blüthgen et al 2020, proximal humeral fractures (Chung et al 2018), ankle fractures (Kitamura et al 2019) and hand, wrist, and ankle fractures (Olczak et al 2017).…”
mentioning
confidence: 99%
“…However, studies using CNNs in the field of orthopedic surgery and traumatology are limited and the field is immature. So far, there are radiographic studies using CNNs for hip fractures (Adams et al 2019, Badgeley et al 2019, Cheng et al 2019, Urakawa et al 2019, distal radius fractures (Kim and MacKinnon 2018, Gan et al 2019, Yahalomi et al 2019, Blüthgen et al 2020, proximal humeral fractures (Chung et al 2018), ankle fractures (Kitamura et al 2019) and hand, wrist, and ankle fractures (Olczak et al 2017).…”
mentioning
confidence: 99%
“…Our CAD system, based on a deep learning algorithm, had some advantages over other symptoms. We conducted a literature review that demonstrated the application of AI-based systems for the diagnosis of hip fracture in Table 4 [17][18][19]. We used the largest amount of learning data from multiple institutions.…”
Section: Discussionmentioning
confidence: 99%
“…However, they did not provide comparisons with health-care professionals (i.e., human vs. machine), and few of the studies reported comparisons with healthcare professionals using the same test dataset. As shown in Table 4, in previous studies on deep learning algorithms for hip fractures, no assessment was made as to how deep learning algorithms affect clinicians' diagnostic abilities [17][18][19].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…32 Detection of Fractures on Radiographs and CT Multiple deep-learning methods have been used to detect fractures on radiographs. Most studies have used open-source CNNs and large training datasets for detecting fractures in multiple body parts including the hip, [33][34][35][36] shoulder, 36,37 wrist, 36,[38][39][40] and ankle 36,41 using the interpretation of experienced radiologists as the reference standard. Diagnostic performance varied but was generally high for all studies, with AUCs ranging between 0.90 and 0.99, sensitivities ranging between 73% and 99%, specificities ranging between 73% and 97%, and accuracies ranging between 75% and 96% ( Table 2).…”
Section: Estimation Of Pediatric Bone Age On Radiographsmentioning
confidence: 99%